Broadband Millimeter-Wave Receiver Front-Ends in Silicon-Germanium Technology for Multi-Band Communication Systems - Nasr, Ismail; Weigel, Robert; Kissinger, Dietmar (IEEE International Microwave Symposium, 2013)
Millimeter-wave frequency-agile front-ends capable of operating at different frequency bands offer an attractive solution for multiband communications. In this paper we present a fully integrated wide-band quadrature receiver covering the two point to point communication bands from 71 to 76 GHz and 81 to 86 GHz and the automotive radar band at 77 GHz. The receiver was fabricated using a low-cost SiGe technology with an ft/fmax of 200/250 GHz. The chip contains a wide-band LNA, Wilkinson power divider, down conversion mixers, two stage polyphase network, VCO, and frequency prescaler. The VCO achieves an ultra high tuning range of 33% between 64 and 89 GHz. Each receiver path (I/Q) has a measured conversion gain between 17 to 23 dB over the operating frequency range. The receiver has a minimum NF of 8 dB, and an input referred compression point of -22 dBm. The complete chip consumes 220mA of current from a 3.3V supply. Index Terms—
elib2cris::1512001600,nasr2013